Non-destructive determination of photosynthetic pigments in the leaves of castor oil plants - doi: 10.4025/actasciagron.v34i3.13872 - João Paulo Gonsiorkiewicz Rigon; Silvia Capuani; Napoleão de Esberard Macêdo Beltrão; José Félix Brito Neto; Valdinei Sofiatti; Fabíola Vanessa França (Acta Scientiarum. Agronomy, 2011)
The aim of the present work was to determine the relationship between photosynthetic pigments extracted in dimethyl sulfoxide (DMSO) and readings obtained by the portable chlorophyll meter, ClorofiLOG® 1030, to generate mathematical models that are able to report the contents of chlorophyll and carotenoids in the leaves of the castor oil plant. This work was conducted at Embrapa Cotton, located in the city of Campina Grande, state of Paraíba, Brazil, in October 2010. For the indirect analysis, portable equipment was used to read leaf discs of different shades of green. The chlorophyll in these discs was then determined using a classical method: 5 mL of DMSO was added, the samples were incubated in a water bath at 70ºC for 30 minutes, and a 3 mL aliquot was removed for spectrophotometric measurements at 470, 646 and 663 nm. The data were subjected to analysis of variance and regression analyses in which the readings obtained using the portable chlorophyll meter were the dependent variable and the photosynthetic pigments that were determined by the classical method were the independent variable. The results indicated that, with the exception of chlorophyll b, the ClorofiLOG® 1030 portable chlorophyll meter estimated the concentration of photosynthetic pigments with high precision, thus saving time and the chemical reagents that are typically used in conventional procedures.